A nonequilibrium binary elements-based kinetic model for benzodiazepine regulation of GABA(A) receptors - Goldschen-Ohm, Marcel P. (The Rockefeller University Press, 2014)
Ion channels, like many other proteins, are composed of multiple structural domains. A stimulus that impinges on one domain, such as binding of a ligand to its recognition site, can influence the activity of another domain, such as a transmembrane channel gate, through interdomain interactions. Kinetic schemes that describe the function of interacting domains typically incorporate a minimal number of states and transitions, and do not explicitly model interactions between domains. Here, we develop a kinetic model of the GABA(A) receptor, a ligand-gated ion channel modulated by numerous compounds including benzodiazepines, a class of drugs used clinically as sedatives and anxiolytics. Our model explicitly treats both the kinetics of distinct functional domains within the receptor and the interactions between these domains. The model describes not only how benzodiazepines that potentiate GABA(A) receptor activity, such as diazepam, affect peak current dose–response relationships in the presence of desensitization, but also their effect on the detailed kinetics of current activation, desensitization, and deactivation in response to various stimulation protocols. Finally, our model explains positive modulation by benzodiazepines of receptor currents elicited by either full or partial agonists, and can resolve conflicting observations arguing for benzodiazepine modulation of agonist binding versus channel gating.